A03 Skeletal muscle mass and its relationship with physical activity and functional status among institutionalised elderly aged 60 and above in Penang - S. W., Ang; Y., Zaitun (Nutrition Society of Malaysia, 2008)
The objective of this study is to determine the skeletal muscle mass (SMM) and its relationship with physical activity and functional status among elderly subjects, aged 60 years and above in the Home for the Infirm and Aged, Penang. A face-to-face interview questionnaire was used to collect the information on personal background and health-related characteristics. Activities of Daily Living (ADL), Instrumental Activities of Daily Living (IADL) and the International Physical Activity Questionnaire (IPAQ) were used to assess the functional status and physical activity. Anthropometric measurements (weight, height, waist, hip, calf and thigh circumferences, body fat mass, body fat percentage and handgrip strength) were measured using appropriate instruments and standard procedures. The anthropometric SMM prediction equation by Lee et al. (2000) was used to determine the SMM value. SMM (kg) = 0.244 x body weight (kg) + 7.80 x height (m) – 0.098 x age (y) + 6.6 x sex (1= male; 0=female) – 1.2 (Asian) – 3.3. A total of 61 elderly (males=47.5%; females=52.5%) participated in this study and their age ranged from 61 to 87 years. Weight (55.28 ± 10.47 kg vs 50.56 ± 10.52 kg), height (162.07 ± 6.48 cm vs 152.34 ± 7.74 cm), and SMM (21.17 ± 2.98 kg vs 12.59 ± 2.78 kg) were significantly higher in males than females. According to age groups, younger respondents (60–69 years) had significantly higher weight (54.27 ± 9.59 kg), Body Mass Index (BMI) (22.12 ± 3.65 kg/m2), and Waist-Hip-Ratio (WHR) (0.90 ± 0.11) compared to older respondents (>70 years). There was no significant association between SMM and ADL scores, IADL and level of physical activity. However, SMM was significantly correlated with handgrip strength (r = 0.637, p < 0.01). Age was not significantly associated with ADL score, IADL score, level of physical activity, SMM and handgrip strength. In conclusion, males and the younger age group had higher SMM, functional status, physical activity, BMI, WHR and other anthropometric measurements. With increasing age, there will be further changes in body composition, decline in functional and physical ability thus affecting health of the elderly. Therefore, the elderly who are at increased risk need to be identified and provided with appropriate intervention programmes or activities.